ΕΛΕΝΗ ΠΑΠΑΡΓΥΡΙΟΥ, Οι συνεργατικές φωτογραφίες Ανδρέα Εμπειρίκου και Μάτσης Χατζηλαζάρου - Παπαργυρίου Ελένη (Σύγκριση/Comparaison/Comparison, 2022)
The collaborative photographs of Andreas Embiricos and Matsi Hatzilazarou This article explores Andreas Embiricos’ and Matsi Hatzilazarou’s collaborative photographs. Made during their marriage in the late 1930s and early 1940s, these images are unique in the history of Greek photography; their experimentality and playfulness sets them apart from the ideologically charged photography produced by professional Greek photographers at the time. These photographs nonetheless prove to be a pivotal moment in the history of Greek surrealism: their technique observes the movement’s international traits, while they are one of the very few occasions in which two surrealist Greek artists join forces to work on a common project. In the first part of the article I discuss the two poets’ photographic archive, while in the second I inquire into an unpublished manuscript by Matsi Hatzilazarou, dated to 1943, containing notes on the photographic illustrations of a book with texts by Odysseus Elytis. Some of these texts were later included in Elytis’ essay collection Open Papers (Ανοιχτά Χαρτιά, 1974); this points to the fact that Elytis at the time envisaged a photographically invested publication resembling André Breton’s books Nadja, Les Vases communicants and L’Amour fou. Despite the fact that the project never came to fruition, the manuscript showcases Hatzilazarou’s intense interest in photography and can be classified as an important surrealist artifact; the notes contain exciting poetic ideas which she thought could be developed into images.